Exceptional poles of local spinor L-functions of GSp(4) with anisotropic Bessel models - Rösner, Mirko; Weissauer, Rainer (Arxiv, 2018)
For non-cuspidal irreducible admissible representations of GSp(4,k) over a local non-archimedean field k, we determine the exceptional poles of the spinor L-factor attached to anisotropic Bessel models by Piatetski-Shapiro.
Gesehen am 25.02.2019